BONINITES OF THE IZU TRENCH - Tararin I.A.; Vasil'yev B.I.; Goivorov I.N. (My University, 1987)
Dredging on the island slope of the Izu Trench brought up volcanic rocks of the marianite-boninite series among fragments of the ophiolite complex. One distinguishing feature of these marianite-boninite rocks is the presence of the nonequilibrium association of high-magnesium olivine, orthopyroxene and clinopyroxene with silicic or intermediate glass. Three angular fragments of tuffaceous boninite lava, 6 to 15 cm in size, were dredged. The boninite-lava fragments consist of phenocrysts of orthopyroxene, clinopyroxene and olivine in a glass matrix, nonuniformly impregnated with minute skeletal crystals and microlites of clinopyroxene. Less commonly, the glass contains acicular crystals of apatite and plagioclase. Chromite crystals no larger than 0.2 mm occur both in phenocrysts and the glass. The principal phenocryst mineral2 is orthopyroxene. Clinopyroxene is the second most abundant phenocryst phase. These and other aspects of the subject are discussed.